PENGARUH CELEBRITY ENDORSER DAN CITRA DESTINASI TERHADAP MINAT BERKUNJUNG WISATAWAN DI DESTINASI WISATA UBUD - Averina Novta; Hanugerah Kristiono Liestiandre; Dewa Ayu Nyoman Aridayanti (JURNAL KEPARIWISATAAN, 2022)
One of the efforts to increase interest of visiting is to design a marketing strategy and one of them is an endorser strategy. Endorsers is celebrities or experts who have expertise, awareness and attractiveness, which can represent the image of the product they promote in order to increase visiting interest. Interest of visiting tourists can appear driven by the quality of information provided through promotional strategies carried out by a tourist destination. This research aims to see the influence of celebrity endorsers and destination image on the interest of visiting tourists in Ubud tourist destinations.This research belongs to the type of research with a quantitative approach. The population in this research is millennial domestic tourists who has visited Ubud and sample a total of 200 respondents. The sampling method in this research used purposive sampling with data collection using a questionnaire distributed online with the help of google form and analyzed technique using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results of the analysis can be concluded that celebrity endorser and destination image hava a significant influence to visiting intention.